The role of the constitutional complaint in the legislative process: Comparative legal aspect - Brovko, Nataliia I.; Medvid, Liudmyla P.; Mahnovskyi, Ihor Y.; Ahmadov, Vusal A.; Leonenko, Maksym I. (Political Questions, 2021)
The article deals with the role of constitutional complaint in the system of quality assurance of the state legislation, for protection of the rights and freedoms. Constitutional complaints, as well as their optimal models, require detailed research. Comparative analysis and survey are the main methods. The subject of a constitutional complaint in the model proposed by the authors may be laws or their individual provisions, regulations of heads of state, government, other statutes and regulations, individual administrative acts, judgements in specific cases. Citizens, foreigners, stateless persons, and legal entities are subjects who have the right to file a constitutional complaint. The authors attribute the following conditions of admissibility of a constitutional complaint: the presence and proof of violation of his/its constitutional rights and freedoms, the use of all other remedies to protect violated rights and freedoms, compliance with deadlines for filing a constitutional complaint in some countries, and payment of state duty. The model proposed by the authors is, however, universal, and further needs to be detailed for countries of interest.